Transfer function analysis between arterial pressure and renal sympathetic nerve activity at cardiac pacing frequencies in the rat - Kanbar, Roy (2007)
This study examined the possible influence of changes in heart rate (HR) on the gain of the transfer function relating renal sympathetic nerve activity (RSNA) to arterial pressure (AP) at HR frequency in rats. In seven urethane-anesthetized rats, AP and RSNA were recorded under baseline conditions (spontaneous HR = 338 ± 6 beats/min, i.e., 5.6 ± 0.1 Hz) and during 70-s periods of cardiac pacing at 6–9 Hz applied in random order. Cardiac pacing slightly increased mean AP (0.8 ± 0.2 mmHg/Hz) and decreased pulse pressure (−3.6 ± 0.3 mmHg/Hz) while leaving the mean level of RSNA essentially unaltered (P = 0.680, repeated-measures ANOVA). The gain of the transfer function from AP to RSNA measured at HR frequency was always associated with a strong, significant coherence and was stable between 6 and 9 Hz (P = 0.185). The transfer function gain measured under baseline conditions [2.44 ± 0.28 normalized units (NU)/mmHg] did not differ from that measured during cardiac pacing (2.46 ± 0.27 NU/mmHg). On the contrary, phase decreased linearly as a function of HR, which indicated the presence of a fixed time delay (97 ± 6 ms) between AP and RSNA. In conclusion, the dynamic properties of arterial baroreflex pathways do not affect the gain of the transfer function between AP and RSNA measured at HR frequency in the upper part of the physiological range of HR variations in the rat